Hemodynamic changes in patients undergoing office‐based sinus procedures under local anesthesia. Issue 1 (5th November 2019) - Chang, Michael T.; Jitaroon, Kawinyarat; Nguyen, Teresa; Yan, Carol H.; Overdevest, Jonathan B.; Nayak, Jayakar V.; Hwang, Peter H.; Patel, Zara M.
Abstract : Background: The objective of this study is to characterize changes in hemodynamics, pain, and anxiety during office‐based endoscopic sinus procedures performed under local anesthesia. Methods: We conducted a prospective study of adults undergoing in‐office endoscopic sinus procedures under local anesthesia. Patients with American Society of Anesthesiologists (ASA) Physical Status Classification System class 1 or 2 were included. Anesthesia was administered by topical 4% lidocaine/oxymetazoline and submucosal injection of 1% lidocaine/1:200, 000 epinephrine. Vital signs and pain were measured at baseline, postinjection, and 5‐minute intervals throughout the procedure. Anxiety levels were scored using the State‐Trait Anxiety Inventory (STAI). Univariate and multivariate regression analyses were performed to identify factors significantly associated with changes in each hemodynamic metric. Results: Twenty‐five patients were studied. This cohort was 52% male, mean age of 57.8 ± 14.4 years, and Charlson Comorbidity Index (CCI) median of 2. Mean procedure duration was 25.0 ± 10.3 minutes. Mean maximal increase in systolic blood pressure (SBP) was 24.6 ± 17.8 mmHg from baseline. Mean maximal heart rate increase was 22.8 ± 10.8 beats per minute (bpm) from baseline. In multivariate regression analysis, when accounting for patient age, cardiac comorbidity, CCI, and ASA, older age was significantly associated with an increase of >20 mmHg in SBP ( p = 0.043). Mean pain score during procedures was 1.5 ± 1.3 with a mean maximum of 4.0 ± 2.6. STAI anxiety scores did not change significantly from preprocedure to postprocedure (32.8 ± 11.6 to 31.0 ± 12.6, p = 0.46). No medical complications occurred. Conclusion: Although patients appear to tolerate office procedures well, providers should recognize the potential for significant fluctuations in blood pressure during the procedure, especially in older patients.